Geração e Propriedades de Superposição de Estados Comprimidos deslocados. - WEBER, Paulo Estevão Rezende (2007)
A feasible scheme for generating squeezed states of superposiçãao displaced in superconducting cavities is presented. The characteristics and properties, especially the non-classical, are studied by means of the Wigner function and Q parameter of Mandel. The probability of successful generation of such superposition are also considered.